Geometric Accuracy Design and Tolerance Allocation of Precision Horizontal Machining Centers - Lina Wang; Xingxing Liu; Wenjie Tian; Dawei Zhang (Machines)
As the structural complexity of machined components increases and the pace of product updates accelerates, the demands for machining precision in CNC machine tools are becoming increasingly rigorous. Consequently, the continuous enhancement of machining accuracy in machine tools presents a significant challenge that must be addressed within the realms of machine tool innovation and the development of manufacturing equipment. This paper conducts a comprehensive investigation into the tolerance optimization allocation method for geometric accuracy in precision horizontal machining centers utilizing interval theory. Initially, a mapping model is developed to represent each source of geometric error and the overall spatial error, drawing upon multi-body system theory. Subsequently, the global maximum interval sensitivity of each geometric error source in relation to the overall spatial model is analyzed. Finally, an interval optimization model for geometric accuracy is formulated based on interval optimization theory, employing a genetic algorithm to address the accuracy allocation problem associated with various error sources in machine tools.